THE CONTRIBUTION OF ARM LENGTH, ARM EXPLOSIVE POWER, BACK TRUNK FLEXIBILITY, FOOTBALL.THROW-IN ABILITY OF TAMANGAPA ELEMENTARY SCHOOL STUDENTS - M. Imran Hasanuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
This research is a type of quantitative descriptive research that uses a "correlational" research design. This study aims to determine:1)Is there a contribution between arm length and throw-in ability?,2)Is there a contribution between arm explosive power and throw-in ability?,3)Is there a contribution between backward trunk flexibility and throw-in ability?,4)Is there a contribution between arm length, arm explosive power, backward trunk flexibility and throw-in ability in soccer games for students of SD Inpres Tamangapa?. The population is students of SD Inpres Tamangapa. The sample used is 35 students of SD Inpres Tamangapa using simple random sampling technique. The data analysis technique is descriptive inferential analysis through the SPSS 25 program at a significance level of α 0.05. The results of the study showed that; 1) There is a contribution between arm length and throw-in ability, amounting to 32.2%, 2)There is a contribution between arm explosive power and throw-in ability, amounting to 24.6%, 3)There is a contribution between backward trunk flexibility and throw-in ability, amounting to 23.9%, 4)There is a relationship between arm explosive power, forward trunk flexibility and arm length together with throw-in ability in soccer games in Tamangapa Elementary School students, amounting to 55.7% and the Fcount value is 12.967.